Semi‐empirical model to estimate ideal conditions for the growth of large protein crystals. Issue 12 (2nd December 2020) - Nakamura, Hirohiko; Takahashi, Sachiko; Inaka, Koji; Tanaka, Hiroaki
Abstract : A semi‐empirical model to estimate the optimum conditions for the growth of large protein crystals has been developed. Abstract : A large high‐quality crystal is required to specify the positions of H atoms in neutron structural analysis. Consequently, several methods have been proposed for obtaining such large crystals, and theoretical considerations for growing them have been presented. However, further investigation is required to obtain a numerical model that can provide quantitative experimental conditions for obtaining a single large crystal. In the case of protein crystallization experiments, the amount of sample is often limited. Therefore, it is more realistic to make a rough estimation from a small number of experiments. This paper proposes a method of estimating the optimum experimental conditions for the growth of large protein crystals by performing a small number of experiments using a micro‐batch method and reporting a numerical model based on nucleation theory and a linear approximation of the crystal‐growth rate. Specifically, micro‐batch experiments are performed to provide the empirical parameters for the model and to help to estimate the conditions for the growth of a crystal of a predetermined size using a certain sample concentration and volume. This method is offered as a step on the path towards efficiently and rationally producing large crystals that can be subjected to neutron diffraction without depending on luck or on performing many experiments. It is expected to contribute to drug design and the elucidation of protein molecular functions and mechanisms by obtaining positional information on H atoms in the protein molecule, which is an advantage of neutron diffraction.